Halal Awareness on Indonesia Consumer - Hanny Nurlatifah; Shohibul Imam (Budapest International Research and Critics University, 2021)
This paper aims to determine the role of halal awareness as a mediating variable of relationship between consumer behavior, religious orientation, and consumer motives towards the purchase intention of halal-labeled food products. This research uses a survey method by conducting structured interviews including questionnaires to 524 respondents who are consumers of halal-labeled food products. The data are analyzed using SMART – Partial Least Square (SMART-PLS– PLS. Based on the result, it is found that halal awareness provides a positive contribution in connecting consumer behavior, religious orientation, and consumer motives towards the purchase intention. The information of the role of halal awareness can be used by the halal product company to formulate marketing strategy for halal products by considering the level of consumer awareness. This research is only limited to the consumers of halal products who are Muslims, and only done in urban areas. So, it can be assumed that the respondents are consumers who have good access to information. Several researches have conducted a study of halal awareness, but this study examines the role of halal awareness variables by involving internal consumer factors such as religiosity and consumer motives in Indonesia in which it is known as a Muslim-majority country. The author agrees with the condition that Muslim communities have a high level of care for searching halal product but for countries with Muslim population domination to have different behaviors and halal awareness can be determining factor in consumer’s decision making.